The concept of svasaṃvedana in Dignāga and Candrakīrti - Nurboo, Tsering (Asian philosophy, 2022)
The concept of reflexive awareness (Sanskrit svasaṃvedana or svasaṃvitti, Tibetan rang rig) is considered an important epistemological notion in the Dignāga tradition of Buddhist pramāṇa theory. The traditionally accepted view is that Dignāga advocates Yogācāra’s notion of reflexive awareness in the Pramāṇasamuccaya and Candrakīrti rejects it altogether. By contrast, the present paper revisits Dignāga and Candrakīrti in the context of svasaṃvedana and argues that Dignāga endorses the antarjñeyavādic notion of svasaṃvedana and Candrakīrti does not negate it at the conventional level. Candrakīrti attacks Dignāga by attributing him as an exponent of Sautrāntrika-Yogācāra notion of reflexive awareness, but his critique does not fundamentally affect Dignāga’s notion of reflexive awareness propounded in the Pramāṇasamuccaya. The submission of the paper is that the fundamental epistemic agenda of reflexive awareness in Dignāga and Candrakīrti is identical, though they diverge methodologically, and it is shown by reexamining Padma dkar po’s interpretation.